6cosx+6secx=13

Simple and best practice solution for 6cosx+6secx=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6cosx+6secx=13 equation:


Simplifying
6cosx + 6secx = 13

Reorder the terms:
6cesx + 6cosx = 13

Solving
6cesx + 6cosx = 13

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Reorder the terms:
-13 + 6cesx + 6cosx = 13 + -13

Combine like terms: 13 + -13 = 0
-13 + 6cesx + 6cosx = 0

The solution to this equation could not be determined.

See similar equations:

| -11x+14=129 | | -3x-20=155 | | =5x-1 | | 11x+9=3x-2 | | 6(3n-4)=(7n+9)+2 | | (9x-9)=(4x+16) | | 3x-3x+12=12 | | 13+3=81 | | x+3.5=25 | | (x+3).5=25 | | 26x-4=100 | | 8=-8x+40 | | (3a-4b)-(2a+5b)= | | -10x^2-42x+330=0 | | -7x^2-3x+72=0 | | 3(3k-1)=4(x+3) | | 2(3x+6)+4(x-1)=-32 | | Y-.45=.15 | | 0.5(x-8)=0.2+11 | | 3x+128=90 | | -3+4p+-2p=1 | | 3x+128=52 | | 27-3x=35 | | 3x+128=180 | | 32-5x=x+44 | | 3x-3+2(x-2)= | | 4xy+6x=0 | | 5x+1=6x+5 | | 2(x-3)-7=6-5(x+1) | | x^2-6x+y^2+2y+44=y | | 4a+8=5a-5 | | 17y-5y^2-12=0 |

Equations solver categories